Blue skies, impacts, and peer review (RT. A Journal on Research Policy and Evaluation, 2013)
This paper describes the results of a survey regarding the incorporation of societal impacts considerations into the peer review of grant proposals submitted to public science funding bodies. The survey investigated perceptions regarding the use of scientific peers to judge not only the intrinsic scientific value of proposed research, but also its instrumental value to society. Members of the scientific community have expressed – some more stridently than others – resistance to the use of such societal impact considerations. We sought to understand why. Results of the survey suggest that such resistance may be due to a lack of desire rather than a lack of confidence where judging impacts is concerned. In other words, it may be less that scientists feel unable to judge broader societal impacts and more that they are unwilling to do so.
Keywords: peer review; impact; expertise; policy; autonomy; evaluation